Comparing biomechanical strength of unicortical locking plate versus bicortical compression plate for transverse midshaft metacarpal fracture - Shanmugam, Rukmanikanthan; Chong, Yin Chyi; Haseeb, Amber; Saw, Aik (SAGE Publications (UK and US), 2018)
Purpose: Metacarpal bone fractures constitute 10% of all fractures. Unstable metacarpal fractures require surgical intervention, which poses danger to flexor tendon either due to bicortical drilling or construct of the implant. Unicortical locking plate fixation may be the solution to preventing flexor tendon injury. Studies have compared locking and compression plates. However, in these studies, the biomechanical properties were tested using the static loading method. This study looks into cyclical loading that is more representative of in vivo conditions, particularly for early rehabilitation. We compared the biomechanical strength of the unicortical locking plate and bicortical compression plate system in a transverse metacarpal fracture, tested with cyclical loading and torsion. Method: Twenty pieces of fourth-generation, biomechanical testing grade, left third metacarpal composite bones were used. Resin was used to create the holding block at both ends of the bone. An oscillating saw with 0.8 mm thick saw blade was used to osteotomize the metacarpal sawbones to create a midshaft transverse metacarpal fracture model. Ten pieces were fixed with a 2.0 mm titanium locking plate via unicortical screw purchase and 10 were fixed with a 2.0 mm, four holes, titanium dynamic compression plate, bicortical purchase of screws. They were subjected to cyclic load to failure testing three-point bending and torsion. Results: There were no significant difference in stiffness and cyclic three-point bending to failure between the unicortical locking plate group and the bicortical compression plate group. The bicortical compression plate group is stiffer and has a higher cyclic bending load to failure as compared to the unicortical locking plate group. Conclusion: Unicortical locking plate fixation of metacarpal fracture can be reliably applied clinically to produce a strong and stable construct that allows early mobilization of the joints. This will not only reduce the complication rate of metacarpal plating, but also improve the functional outcome of the hand.